Sustainability and Territoriality:: Crafting the Fight and the Resistance of Rural Women in Brazil - Gomes, Debir Soares; Esmeraldo, Gema Galgani Siliveira Leite (Sustainability in Debate, 2014)
The article is outlined from the analysis of a case study research realized in the context of actions of women in the Maceió settlement, located in the county of Itapipoca, in the state of Ceará. Working with social relations and reproduction strategies of the lace-making and peasant women, the sustainability and territoriality categories are being operated for the comprehension of their practices and their world views. Collectively organized, they produce a material and mainly symbolic value, by relating their handicraft work to the territoriality and the socio-environmental sustainability of the settlement. Through their forms of inclusion into the spaces of power and production, they constitute new identities, promote the participation and the selfacknowledgment in the use and occupation of the beach and the sea, in the organization of the settlement, in the groups of extraction and beneficiation of seaweed and in the struggles involving the construction of territorialities.